1990
DOI: 10.1097/00132582-199004000-00033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Open-End (Single Hole) and Closed-End (Three Lateral Holes) Epidural Catheters Complications and Quality of Sensory Blockade

Abstract: A randomised, single-blind study was conducted on 802 parturient women who required epidural analgesia, to compare open-end (single hole) with closed-end (three lateral holes) epidural catheters. The complication rate after catheter insertion was not statistically drferent between the two groups, but the number of unsatisfactory blocks was significantfy higher in the open-end group (p < 0.001). The closed-end catheters were easier and less painful to place, but gave a higher incidence of bloody taps. The open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
2
11
0
2
Order By: Relevance
“…There is no ideal method for identification of intravascular catheter location [9][10][11][12][13][14][15]. The preference for patient position during the procedure is variable [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…There is no ideal method for identification of intravascular catheter location [9][10][11][12][13][14][15]. The preference for patient position during the procedure is variable [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Kinking has already been discussed above, catheter ‘occlusion’ is likely to be the result of a block of the single terminal orifice of smaller catheters. Interestingly, in a comparison of similar single endhole and multiple lateral‐hole catheters in obstetric patients, it was found that unsatisfactory sensory blockade was more common with the single terminal orifice catheter ( 5). Leakage of the infusate around the catheter is common in paediatric patients and is more frequent with decreasing age and weight.…”
Section: Discussionmentioning
confidence: 99%
“…Дані про те, що катетери з декількома отворами мають значно нижчу частоту неповного епідурального блоку підтверждені рядом авторів [7,8]. У їх підтримку Segal і співавт.…”
Section: о б го во рен н я резул ьтат і в д о с л і д ж ен н яunclassified